Online classroom lounge - Abdullah, Shamsuddin; Antaken @ Nurhidayah Abdullah, Halen; Hamzah, Haliza; Ismail, Nur Farrah Syazwanie (Centre for Teaching and Learning (CTL) and International Islamic University Malaysia (IIUM), 2018)
Classrooms nowadays have gone beyond the physical walls in which internet connectivity was used for teaching and learning purposes. One of many ways is Online Classroom (OC) which means synchronous instructor-dependent classroom hours, conducted online. Lecturers have been conducting Online Classroom independently for many purposes such as replacing classes and integrating blended learning techniques. However, without a standard guideline, lecturers are open to risk of malpractice when conducting OC. A committee was formed to conduct a pilot test on OC in order to collect feedback from lecturers and students. This feedback was then used to establish standard guidelines for lecturers in conducting OC. A platform is then needed to house this guideline and connect lecturers to share and improve their OC practices. Therefore, the Online Classroom Lounge (OCL) is created as a web platform allowing lecturers to share their OC pedagogies. This platform also allows lecturers and students to provide feedback on these pedagogies in order to minimize the risks before implementation of OC. The contents of the OCL include: A page (OC guidelines) containing standard guideline to implement OC; a second page (OC forum) showcasing OC pedagogies shared by lecturers and students with likes and comments section; and a third page (open lounge) is an open platform for students and lecturers to discuss other OC-related matters. The OCL is focused to cater the needs of the Centre for Foundation Studies community. As compared to i-Hikmah (a portal of Community of Practice for IIUM), the OCL has the valueadded features such as ‘Like’ function, public access without the need to login in from IIUM, and faster access to OC-related discussion.